Regulating finance : balancing freedom and risk - Padoa-Schioppa, Tommaso (Oxford ; New York : Oxford University Press, 2004)
Grounding its analysis in the historical evolution of financial regulation, this book addresses a range of public policy issues that concern the design of financial regulation and its enforcement, and contributes several new ideas to the debate in this field. Financial systems have become more competitive across sectors of financial institutions and nations, and direct regulations have been removed in pursuit of efficiency. However, as the risk of institutional failures has increased, de-regulation has had to be followed by re-regulation. In which form should this happen? This book answers the question.
Essays originally presented between 1997 and 2002 as lectures, speeches, a conference paper and a panel discussion.
Includes bibliographical references (p. [136]-140) and index.
rpm 09/05/13, rpm 31/08/16
Loans
Keywords: Financial institutions; Banks and banking; Banking law; Banks and banking, Central